Marx's Capital : Hegelian Sources - Blunden, Andy, (Social Sciences E-Books Online, Collection 2026., 2026)
Following the companion volume, The Capital/Logic Debate, Blunden presents a systematic presentation of the Hegelian structure of the three volumes of Capital . It is shown that Capital contains three distinct layers of structure, originating from Marx's reading of Hegel's Logic and his Philosophy of Right . Capital reflects Marx's critique of the Political Economists, his unique appropriation of economic history and an application of the method outlined by Hegel in his Logic and applied to his Encyclopaedia . These insights into Capital are presented here for the first time.